Leadership Practice for Building Trust of Followers: Decisive Factors of Organizational Performance - Ba Phong Le; Quang Thang Tran (SEISENSE (PRIVATE) LIMITED, 2020)
Purpose - Leadership plays a decisive role in key organizational outcomes. To investigate the effects of leadership and its mechanism on organizational performance, this paper examined how transformational leadership impacts followers’ trust for improving operational and financial performance in the case of Vietnamese firms. Design/Methodology - This study used the Structural Equation Modeling to assess the correlation among the constructs based on using survey data of 285 employees at 60 manufacturing and service companies. Findings - The findings revealed that employees' trust in leadership acts as a mediating mechanism in the relationship between transformational leadership and organizational performance. The transformational leadership style of leaders has greater effects on financial performance, while employee’s trust has larger effects on operational performance. This study calls attention to the importance of raising employee trust to link transformational leadership and organizational performance. Practical and theoretical implications - From a practical point of view, the paper brings more knowledge and insights for CEO/managers on the right pathway to enhance organizational performance. The paper also provides theoretical initiatives on the leadership theory and the new pathway to promote operational and financial performance.